Traces of epistemological changes in the field of Portuguese as an Additional Language: the Celpe-Bras exam as a mechanism of language policies - Martins, Alexandre Ferreira (BELT - Brazilian English Language Teaching Journal, 2018)
The following text discusses the epistemological changes in the field of Portuguese as an Additional Language (PAL), in Brazil, in the years that preceded the establishment of the Certificate of Proficiency in Portuguese for Foreigners (Celpe-Bras). Therefore, this exam is understood as a mechanism of de facto linguistic policies, related to the ideological model of linguistic policies by Shohamy (2006), considering an approach for its importance in the development of the field of PAL in Brazil. The debate pertaining to the epistemological changes, which are noticeable in academic publications, is revealed considering its relations with the theoretical postulates of the Celpe-Bras. These changes can be found mostly in thesis and dissertations selected based on the revision of the gathering of academic works performed by Furtoso (2015). This mechanism, from 1998 onwards, validates and expands the criticism and reinterpretation present in the production of the field, before its emergence. Its construction followed the epistemological changes of the area of study and systematized the main reflections concerning the proficiency in an additional language.